Protein kinase C enhances plasma membrane expression of cardiac L-type calcium channel, CaV1.2. Issue 6 (2nd November 2017) - Raifman, Tal Keren; Kumar, Prabodh; Haase, Hannelore; Klussmann, Enno; Dascal, Nathan; Weiss, Sharon
ABSTRACT: L-type-voltage-dependent Ca 2+ channels (L-VDCCs; CaV 1.2, α1C ), crucial in cardiovascular physiology and pathology, are modulated via activation of G-protein-coupled receptors and subsequently protein kinase C (PKC). Despite extensive study, key aspects of the mechanisms leading to PKC-induced Ca 2+ current increase are unresolved. A notable residue, Ser1928, located in the distal C-terminus (dCT) of α1C was shown to be phosphorylated by PKC. CaV 1.2 undergoes posttranslational modifications yielding full-length and proteolytically cleaved CT-truncated forms. We have previously shown that, in Xenopus oocytes, activation of PKC enhances α1C macroscopic currents. This increase depended on the isoform of α1C expressed. Only isoforms containing the cardiac, long N-terminus (L-NT), were upregulated by PKC. Ser1928 was also crucial for the full effect of PKC. Here we report that, in Xenopus oocytes, following PKC activation the amount of α1C protein expressed in the plasma membrane (PM) increases within minutes. The increase in PM content is greater with full-length α1C than in dCT-truncated α1C, and requires Ser1928. The same was observed in HL-1 cells, a mouse atrium cell line natively expressing cardiac α1C, which undergoes the proteolytic cleavage of the dCT, thus providing a native setting for exploring the effects of PKC in cardiomyocytes. Interestingly, activation of PKC preferentially increased the PM levels of full-length, L-NT α1C . Our findings suggest that part of PKC regulation of CaV 1.2 in the heart involves changes in channel's cellular fate. The mechanism of this PKC regulation appears to involve the C-terminus of α1C, possibly corroborating the previously proposed role of NT-CT interactions within α1C .